2012
DOI: 10.1007/s10903-012-9672-9
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy in Korean Immigrants at Risk for Type 2 Diabetes

Abstract: Rising incidence of type 2 diabetes (DM) in Korean immigrants has highlighted the need for better prevention efforts. Health literacy is an important predictor in the utilization of preventative health measures, however little is known about health literacy in Korean immigrants. This study examined DM risk factors in a sample of 145 at-risk Korean immigrants, their level of health literacy, and associations between health literacy and DM risk factors. Findings indicated a high prevalence of DM risk factors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…Although the results of this study cannot be generalised to a larger population due to design limitations, research has shown that similar barriers such as low health literacy, linguistic issues and lack of insurance negatively affect Korean immigrants with type 2 diabetes in terms of obtaining preventive care and health information. 28 Second, it was observed that the percentage of male participants in the current study was much higher than the female counterparts (62% and 38%, respectively). This phenomenon may be due to the fact that many female immigrants had to rely on transportation support from family members; thus they were not able to join the study despite being invited.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Although the results of this study cannot be generalised to a larger population due to design limitations, research has shown that similar barriers such as low health literacy, linguistic issues and lack of insurance negatively affect Korean immigrants with type 2 diabetes in terms of obtaining preventive care and health information. 28 Second, it was observed that the percentage of male participants in the current study was much higher than the female counterparts (62% and 38%, respectively). This phenomenon may be due to the fact that many female immigrants had to rely on transportation support from family members; thus they were not able to join the study despite being invited.…”
Section: Discussionmentioning
confidence: 48%
“…The findings of the current study echoed previous studies in which similar barriers, such as a lack of health insurance, negatively affected Korean immigrants’ ability to obtain diabetes preventive care and health information. 28 Asian immigrants were also found to be disadvantaged in terms of obtaining healthcare due to linguistic barriers, cultural incompetence regarding American health systems, lack of insurance and being discriminated against in the healthcare system. 29 Thus, the findings of the current study may not only be restricted to Chinese American immigrants but may also extend to other ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…A current study in Sweden reported a 60 % rate of inadequate health literacy among refugees, and factors such as being born in Somalia were associated with an increased risk of having an inadequate health literacy [25]. Health literacy is an important predictor in the utilization of preventative health measures among immigrants [28, 29], with the literature suggesting that any future efforts to improve equity in disease prevention may require an improved health literacy of immigrants [27]. Nonetheless, despite Somali women in Norway being reported to have higher rates of overweight and obesity [7], a high risk of diabetes that increases with the duration of residence in Norway and a lower utilization of preventive health services, the level of health literacy among this group has never been studied in Norway.…”
Section: Introductionmentioning
confidence: 99%
“…One study found a correlation between the health literacy level of Korean migrants and the risk factors for type 2 diabetes [13]. Moreover, poor health literacy and poor care were found to be correlated with HIV infection among the African American population [14].…”
Section: Introductionmentioning
confidence: 99%